1996
DOI: 10.1093/qjmed/89.12.933
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella bacteraemia: community versus nosocomial infection

Abstract: In the period 1988-1993, 241 patients had Klebsiella bacteraemia at our medical centre. The annual number of patients with positive blood cultures increased from 306 in 1988 to 622 in 1993, representing a 4.5-6% positivity rate of drawn cultures. After E. coli, Klebsiella was the leading cause of Gram-negative bacteraemia. During this period, the absolute number of Klebsiella bacteraemia increased from 25 in 1988 to 84 in 1993; this represents a true increase in Klebsiellaa bacteraemia, from 6-7% of positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 38 publications
1
67
1
1
Order By: Relevance
“…Some of the bacterial species implicated in bloodstream infections are Klebsiella sp. and Escherichia coli [6]. This study therefore is to screen the blood of HIV-1 patients in the studied community for the types of bacterial pathogens present and to know the antibiogram profile of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the bacterial species implicated in bloodstream infections are Klebsiella sp. and Escherichia coli [6]. This study therefore is to screen the blood of HIV-1 patients in the studied community for the types of bacterial pathogens present and to know the antibiogram profile of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella (K.) pneumoniae is a frequently isolated causative pathogen in lower respiratory tract infection. [1][2][3] The high incidence of pneumonia and the increasing resistance of respiratory pathogens to antimicrobial agents stress the importance of gaining more insight into the pathogenesis of this infection. 1,4 CD44 is a transmembrane adhesion molecule known to be involved in binding and metabolism of hyaluronan (HA).…”
mentioning
confidence: 99%
“…Some studies showed that Klebsiella was one of the leading causes of Gram-negative bacteraemia in the general population [25]. SLE patients infected with Klebsiella were found to have lower probabilities of 14-day survival [26] in a study analysing the short-term survival of patients with SLE after bacteraemia episodes.…”
Section: Klebsiellamentioning
confidence: 99%